(untitled) (Global Journal of Human-Social Science, 2016)
This study has been an attempt to determine factors influencing academic achievements of grade 10 students (normally under age 18 years) on specific subjects. A crosssectional survey was conducted on a total of 719 sample students of grade 10 from 11 different government and non-government secondary schools using multistage sampling technique. A designed questionnaire was used to obtain data from the respondents. The secondary data on students EGSECE scores were obtained from the Education Department as achievements of students in the five selected subjects: Mathematics, Biology, Physics, Chemistry and English. Descriptive analysis, factor analysis and multivariate multiple linear regression analyses were used to analyze the data. From the descriptive results both governmental and non-governmental school students were achieved poorest in physics and best in English. However, on average, non-governmental school students’ achievements were better than governmental school students.